Thyroid nodules of indeterminate cytology in Hispanic/Latinx patients. Issue 8 (18th May 2022) - Kerr, Catherine E.; Ferrell, Jay; Kitano, Mio; Koek, Wouter; Dahia, Patricia L. M.; Velez, Jorge; Francis, Gary
Abstract: Background: Behavior of differentiated thyroid cancer (DTC) varies among ethnic groups. Recommended management of thyroid nodules with indeterminate cytology (TN‐IC) is based on molecular analysis from predominantly non‐Hispanic white patients. We hypothesized that TN‐IC in Hispanic/Latinx patients would have different features, management, and outcomes and that molecular testing might perform differently in Hispanic/Latinx patients. Methods: Retrospective chart review was performed on 127 TN‐IC analyzed with Afirma. Patient characteristics were compared using linear model ANOVA and Fisher's exact test. Results: Out of 127 TN‐IC, 71 (56%) were Hispanic/Latinx. Hispanic/Latinx had a greater prevalence of diabetes, but Afirma results (benign or suspicious) were similar between ethnic groups. Fourteen patients had malignant pathology. Their management and outcomes were similar across groups. The negative predictive value for our cohort (97.9%) was similar to published data. Conclusions: Data from our predominantly‐Hispanic/Latinx cohort suggest that Afirma performs similarly in Hispanic/Latinx and non‐Hispanic white patients with TN‐IC.